Digital Tourism Promotion: Social Media, E-WOM, and Celebrity Endorsement in Jakarta - Catur Widayati; Fadhila Dhia Malihah; Hasliza Abdul Halim (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
The COVID-19 pandemic has caused unprecedented disruptions to the global tourism industry, with the absence of tourists and flight restrictions exacerbating challenges for tourism-dependent economies like Indonesia. This study examines the socio-economic impact of the pandemic on Jakarta's tourism sector, focusing on the effectiveness of large-scale social restrictions (PSBB), economic repercussions, and long-term resilience strategies. The research highlights the role of Social Media Advertising, Electronic Word of Mouth (E-WOM), Celebrity Endorsements in influencing tourist behavior. Using a sample of 260 respondents who engaged in tourism activities, the data was analyzed through Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings reveal that Brand Image positively influences Visit Intention, while Celebrity Endorsement directly affects Visit Intention but not Brand Image. E-WOM and Social Media Advertising positively impact both Brand Image and Visit Intention. These results provide valuable insights for policymakers in navigating pandemic recovery strategies for Jakarta’s tourism sector.